(untitled) (Productivity, 2020)
This research aims to determine the influence of living (X1) and the Price (X2) on the purchase decision (Y) on Starbucks Manado Town Square. This approach uses a quantitative approach, with a sample of 100 respondents using a Likert scale. The technique of collecting data in this research is by using online questionnaire deployment. The analytical techniques used in this study use double Linear analysis techniques. The data that has fulfilled the analytical techniques is processed using SPSS program tools (Statistical Package for Social Sciences). The results of this study indicate that lifestyle and prices have a significant positive effect on purchasing decisions.